An acoustic emission sensor system for thin layer crack detection. (September 2018) - Unterreitmeier, M.; Nagler, O.; Pfitzner, L.; Weigel, R.; Holmer, R.
Abstract: We present a new method for semiconductor layer characterization enabling simultaneous crack generation and detection based on the established acoustic emission testing. In this paper, we explain the test concept and failure mechanism of diamond tip indentation with acoustic wave measurement on oxide layers by analytical modeling and computer-aided simulations. For this purpose, an innovative design of a sensor-indenter system was developed and experimentally verified. In further tests, the new acoustic crack detection method is correlated with proven optical inspection methods and the good reproducibility of the measurement is demonstrated. The high sensitivity and resolution of this method offer new opportunities for thin layer characterization at lower time and cost. The new high-efficient method can be used especially for process qualification for semiconductor wafer test, where oxide cracks can be induced by sharp probes causing electrical failure of the chip. Highlights: New acoustic emission test method for thin layer characterization enabling simultaneous crack generation and detection by nano-indentation. Development of a sensor-indenter system with high acoustic signal sensitivity for crack detection in real-time. Acoustic crack detection in nano-scale dimensions, which are almost invisible by optical inspection. Applicable especially for semiconductor wafer test process qualification. Faster and more reliable inspection method compared to today's standard.